Dynamic analysis of an L-shaped liquid-filled pipe with interval uncertainty. (1st March 2022) - Guo, Xumin; Cao, Yiming; Ma, Hui; Xiao, Chunliang; Wen, Bangchun
Highlights: An L-shaped liquid-filled pipe model with elastic support containing both straight pipe and continuous curved pipe models is established. An uncertain frequency response surrogate function (UFRSF) is proposed to evaluate the uncertainty of the liquid-filled pipe. The frequency responses of the liquid-filled pipe are analyzed when the pipe parameters, support parameters, and fluid parameters are uncertain. Abstract: In this paper, a fourteen-equation fluid-structure coupling model of an L-shaped liquid-filled pipe with elastic support is established by the transfer matrix method (TMM). The validity of the dynamic model of the liquid-filled pipe is verified by comparing the frequency results obtained from the literature, experiment, and finite element method. The liquid-filled pipe system is inevitably subject to uncertainties due to the manufacture and assembly error, material dispersion, and the change of working conditions. To obtain more reasonable evaluations of the dynamic response of the L-shaped liquid-filled pipe, an uncertain frequency response surrogate function (UFRSF) is proposed to evaluate the uncertainty of the liquid-filled pipe. The pipe parameters, support parameters, and fluid parameters are taken as unknown but bounded interval variables. The frequency responses of the L-shaped liquid-filled pipe under various uncertain variables are calculated. Compared with the Monte Carlo simulation (MCS) results, the efficiency and accuracy of the proposed method for solving the uncertain frequency response of liquid-filled pipe are proved. The proposed method has the advantages of convenience in implementation, high efficiency and transparency, and can provide theoretical guidance for the uncertainty assessment of liquid-filled pipes with unknown sample probability distribution in engineering. Graphical abstract: Image, graphical abstract